Studi Tentang Enzyme Untuk Industri Tekstil - Achmad Soelaeman (Balai Besar Kimia dan Kemasan, 1985)
Enzyme int the textile industries is used to eliminate starch, while the starch is used to strengthen the yam to be made textile. To facilitate the next process, forexample immersing, dying and printing then the starch elimination process in developed. The starch elimination can be carried out by various process, among other things is using the enzyme.